PEDAGOGICAL CONDITIONS FOR THE FORMATION OF PROFESSIONAL COMPETENCE OF FUTURE PRESCHOOL EDUCATORS USING THE «Sibboard» TECHNOLOGY - Numonjonova Farangiz Komilovna (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract: This article explores the pedagogical conditions necessary for effectively forming professional competence in future preschool educators through the use of the interactive educational platform «Sibboard». The study examines how integrating «Sibboard» technology into the educational process enhances students’ practical skills, motivation, and collaborative abilities. Employing a mixed-methods research design, including literature review, observation, surveys, and a pedagogical experiment, the study identifies key conditions that support interactive learning and competence development. The results demonstrate that targeted pedagogical strategies combined with «Sibboard» technology significantly contribute to the professional readiness of preschool educator students.